The therapeutic potential of purified cannabidiol - Saoirse Elizabeth O'Sullivan; Sanne Skov Jensen; Gitte Nykjaer Nikolajsen; Heidi Ziegler Bruun; Rhenu Bhuller; Julia Hoeng (BMC, 2023)
Abstract The use of cannabidiol (CBD) for therapeutic purposes is receiving considerable attention, with speculation that CBD can be useful in a wide range of conditions. Only one product, a purified form of plant-derived CBD in solution (Epidiolex), is approved for the treatment of seizures in patients with Lennox-Gastaut syndrome, Dravet syndrome, or tuberous sclerosis complex. Appraisal of the therapeutic evidence base for CBD is complicated by the fact that CBD products sometimes have additional phytochemicals (like tetrahydrocannabinol (THC)) present, which can make the identification of the active pharmaceutical ingredient (API) in positive studies difficult. The aim of the present review is to critically review clinical studies using purified CBD products only, in order to establish the upcoming indications for which purified CBD might be beneficial. The areas in which there is the most clinical evidence to support the use of CBD are in the treatment of anxiety (positive data in 7 uncontrolled studies and 17 randomised controlled trials (RCTs)), psychosis and schizophrenia (positive data in 1 uncontrolled study and 8 RCTs), PTSD (positive data in 2 uncontrolled studies and 4 RCTs) and substance abuse (positive data in 2 uncontrolled studies and 3 RCTs). Seven uncontrolled studies support the use of CBD to improve sleep quality, but this has only been verified in one small RCT. Limited evidence supports the use of CBD for the treatment of Parkinson's (3 positive uncontrolled studies and 2 positive RCTs), autism (3 positive RCTs), smoking cessation (2 positive RCTs), graft-versus-host disease and intestinal permeability (1 positive RCT each). Current RCT evidence does not support the use of purified oral CBD in pain (at least as an acute analgesic) or for the treatment of COVID symptoms, cancer, Huntington's or type 2 diabetes. In conclusion, published clinical evidence does support the use of purified CBD in multiple indications beyond epilepsy. However, the evidence base is limited by the number of trials only investigating the acute effects of CBD, testing CBD in healthy volunteers, or in very small patient numbers. Large confirmatory phase 3 trials are required in all indications.